Intensity of consumer education and consumer empowerment among Malaysian consumers - Tajurahim, Nurul Nadiah Syahida; Abu Bakar, Elistina; Md Jusoh, Zuroni; Muhammad Arif, Afida Mastura; Ahmad, Sa'odah (Malaysian Consumer and Family Economics Association, 2019)
Today, in the era of globalization, the evolution of internet technology has caused market conditions to become complicated and complex. Consumers of all ages are exposed to a wealth of information and commerce 24 hours a day. Also, a variety of choices and offers to consumers make the decision making more complicated. Thus, consumers need to be empowered to protect themselves in the market. Utilizing Empowerment Theory, this paper seeks to analyze the influence of intensity of consumer education on consumer empowerment among Malaysian consumers. A total of 400 respondents had participated in this research where they were selected using multistage probability sampling. The data were collected using a self-administered questionnaire and were analyzed using SPSS software. Pearson Correlation Test is conducted to examine the relationship between the variables. The t-test is then used to examine the differences in consumers' level of empowerment among urban and rural consumers. The findings reveal that the intensity of consumer educations was positively related to consumer empowerment. Moreover, there is no significant difference between urban and rural consumers regarding the level of consumer empowerment. The results can significantly contribute to improving the current consumer policy and consumer education in Malaysia.